Confounding Risk Factors in Developing Type 1 Diabetes Mellitus among Children and Adolescents at Sulaimani Chronic Diabetes Health Center: Diabetic and risk factors - Azize, Pary Mohammad; Sadiq, Chia H. (Kurdistan Journal of Applied Research, 2021)
Diabetes mellitus is one of the most common chronic health condition worldwide and the most common endocrine disease in children and adolescences. The aim of this study is to find out the risk factors, which lead to pathogenesis of type 1 diabetes mellitus among children and adolescent in diabetes health center Suleimani city. A descriptive cross sectional study was conducted at a special center for Type 1 Diabetes Miletus A questionnaire was developed and administered to a convenience sample of (170 ) mothers or fathers. Descriptive statistics data (frequency, percentage, mean and stander deviation) and also Factorial analysis (principal component analysis) was used in order to identify the effective factors affecting diabetes in children and Adolescents. The finding show that, 39.4 % of samples were aged between (9-13) years old, which stated as the highest rate among all age groups, while the minority of age was between (1-4) years old, which was equal to 8.2% of the total and the (Mean ±S.D) was equal to 10.44±4.04 respectively. The majority of age at diagnosis was between (5-8) years old, which is 35.3% and their food habit was normal diet, which is 73.5%, while the Sugar diet and Fatty diet were 25.9% and 0.6%y respectively. Most of the participants, 19.4% of family history was Type 2 diabetes, which was the first rank of the family history and majority of them were Kurdish in nationality. Age at diagnosis and mode of delivery considered as the first factor affect the type 1 diabetics mellitus. The second most common factor effect on diabetes disease in children and adolescents are maternal habit and maternal disease followed by Gestational age at birth and Neonatal disease, then food habits, Neonatal weight was estimated as the fourth component factors affecting Type 1 diabetes mellitus. Residency and Family history of autoimmune disease were ranked in the fifth line of factor, finally the weakest factor is nationality by total variance of 8.552%. The first years of life is play an important role in triggering and the development of type 1 diabetes mellitus among children and adolescent , also maternal diseases ( gestational diabetes, pre-eclampsia and perinatal infection during pregnancy), healthy diet during pregnancy and education programs are recommended